(3MGTjI Ydi TQM LZejfjs - (3GdHQLfOj, YHO GdYdj Hf eMeO Hf MSjf, HYO (B935 (3g`s ((3eMeO (B( )s)
(3ChdgG (B:s
(3GdMeO ddg QH GdeTGQb hGdeZGQH eRjf GdSeGA HGdchGcH agPg JYdjbGJ Ydi GdehGVY GdeTcdI hJfHjgGJ Ydi QehR GdeHGMK GdNajIGdeYVdI ef TQM GdedNU aj GdgjFI GdfShH Edi aGVd GdCFeI bGVj RGOIs
(3BNQgG (B:s
(3hgPg GdSfI GdbeQjI GdhSWjI fGbUI Yf GdSfI GdTeSjI hGMOI aEf OhQ GdhSW OhQ GdJbhje aj GdTeS QKJeGf aj ReGf hGMO hEfeG GdJaGhJ Hjf GdTgQ GdTeSjI GdhSjWI Jes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4\30s
(3cTa GdXfhf (B2\1918s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3Gdadc hGdJfLje hGdejbGJs